2017
DOI: 10.1002/jtr.2132
|View full text |Cite
|
Sign up to set email alerts
|

Surviving the recession with efficiency improvements: The case of hospitality firms in Portugal

Abstract: During a recession, lower profitability limits investments in new initiatives; significant cost‐cutting could deteriorate service levels; and sticky tangible and intangible resources limit a hospitality establishment's ability to reduce its asset base. Limited ability to cut costs or reduce asset base shifts the focus on improving efficiency. Drawing on panel data of 1,647 Portuguese hospitality establishments from 2007 to 2014, we find that an increase in the return on fixed assets made the highest contributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Energy efficiency (EE) provides an opportunity to substantially reduce energy consumption and consequently GHG emissions from the services sector (Hrovatin et al 2016 ; Liang et al 2019 ; Schleich 2009 ; Schlomann and Schleich 2015 ) and also to reduce energy-related running costs in that sector (Mavrotas et al 2003 ; Patel and Guedes 2017 ; Sakshi et al 2020 ). Several studies have analysed the potential energy savings, avoided CO 2 emissions and profitability of EE investments (Cattaneo 2019 ; Fleiter et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Energy efficiency (EE) provides an opportunity to substantially reduce energy consumption and consequently GHG emissions from the services sector (Hrovatin et al 2016 ; Liang et al 2019 ; Schleich 2009 ; Schlomann and Schleich 2015 ) and also to reduce energy-related running costs in that sector (Mavrotas et al 2003 ; Patel and Guedes 2017 ; Sakshi et al 2020 ). Several studies have analysed the potential energy savings, avoided CO 2 emissions and profitability of EE investments (Cattaneo 2019 ; Fleiter et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…The analysis focuses on the household, services and transport sectors in Spain, which between them account for about 75% of the country's energy consumption (IDAE 2017). EE provides an opportunity to reduce energy consumption in the household sector (Linares and Labandeira 2010;Ramos et al 2015) and in the accommodation and transport sectors (Schleich 2009;Schlomann and Schleich 2015) and to reduce energyrelated running costs in the services sector (Patel and Guedes 2017;Sakshi et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The study confirmed IC’s substantial influence on strategic and financial performance. Patel and Guedes (2017) assessed IC in 1,647 Portuguese hospitality firms (2007–2014) using Return on Intangible Assets (ROIA). Findings suggested that increasing returns on fixed and intangible assets significantly affected operating profit.…”
Section: Resultsmentioning
confidence: 99%